ENGLISH AND ARABIC LITERATURE STUDENTS, MUST HAVE TOEC PREPARATION COURSE? - Dwi Maro Yuwono (Vol. 3 No. 2 (2025): Special Issue: Cultural Resilience and Digital Literacy for a Diverse Society, 2025)
The effectiveness of learning is a complex and multidimensional problem. researcher conducted an intensive evaluation of the implementation of TOEC Preparation Course carried out by the Sunan Kalijaga UIN Language Center especially for students of English Literature and Arabic Literature department of UIN Sunan Kalijaga Yogyakarta. The evaluative method used in this study was the CIPP approach. Retrieving data using survey and interview techniques. The results of evaluative research on the implementation of TOEC Preparation Course indicate that each participant's have positive reaction to the implementation of the program. It has influenced the level of mastery of knowledge and skills mastered by each participant. However, it does not have a significant impact on the quality of the learning process carried out by participants. There are variables that bring the desired impact of the program implementation to motivate of each participant to apply knowledge and skills obtained that they have learned in their department.